Analysis of the mechanism of Erchen decoction in treating chronic bronchitis based on network pharmacology and molecular docking - Yanshan HE; Rui WANG; Jinlian ZHU; Yingjia DENG; Yafang DENG; Yuanning ZENG; Qiuhong WANG (Journal of Holistic Integrative Pharmacy)
[Abstract]: Objective: In this study, we used network pharmacology to explore the main targets and signaling pathways of Erchen decoction in the treatment of chronic bronchitis. Methods: The effective active ingredients of Erchen decoction were screened through the traditional Chinese medicine systems pharmacology database and analysis platform, and the relevant protein targets of chronic bronchitis were retrieved through the GeneCards database using the STRING platform to construct a protein–protein interaction network. Cytoscape software was used to construct drug-component-target network diagrams. Gene Ontology analysis and Kyoto Encyclopedia of Genes and Genomes pathway analysis were performed on the intersection target genes. Results and conclusion: After database analysis, 256 active ingredients in Erchen decoction were screened as well as 110 targets related to chronic bronchitis and 188 related signaling pathways. Erchen decoction was found to play a potential role in the treatment of chronic bronchitis by regulating inflammation, immunity, cough, and phlegm and other multiple targets and multiple pathways.